2012
DOI: 10.2298/abs1202573m
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of bottle gourd Lagenaria siceraria (Mol.) Standley and its morphological characterization by multivariate analysis

Abstract: A wide range of bottle gourd Lagenaria siceraria (Mol.) Standley germplasm was collected from different parts of the world. Genetic resource preservation and determination of genetic variability was carried out as a foundation for future breeding work. The germplasm diversity collected in Serbia is a result of its adaptation to diverse ecological conditions and farmers’ selection in accordance with their preference and ethnobotanical utilization. The broad intraspecific variation of the plant, fruit and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
16
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 11 publications
7
16
1
9
Order By: Relevance
“…Similar results were also reported by Gautam (2013) in ridge gourd, Trimech et al, (2013) in muskmelon, Mladenovic et al, (2012) in bottle gourd.…”
Section: Principal Component Analysissupporting
confidence: 90%
“…Similar results were also reported by Gautam (2013) in ridge gourd, Trimech et al, (2013) in muskmelon, Mladenovic et al, (2012) in bottle gourd.…”
Section: Principal Component Analysissupporting
confidence: 90%
“…Concerning the selection process during long cultivation history, Fuller and Allaby (2009) suggested that different selective pressures occurred different organs as target f selection. Similar argument was advocated by Mladenovic et al (2012) in their study on morphological characterization of Lagenaria siceraria based on multivariate analysis on fruit and seeds morphology. This study revealed that morphological variability on fruit and seeds in L.siceraria was resulted from selection process based on preferences on particular shapes and size of fruit.…”
Section: Discussionsupporting
confidence: 58%
“…Earlier, Fayeun et al (2016) reported genetic variability among 21 fluted pumpkins for seedling traits. Morphological differences are commonly reported among cucurbits (Mladenovic et al, 2012).…”
Section: Discussionmentioning
confidence: 99%